Airport Flight-Gate Allocation Assignment Using Local Antimagic Vertex Coloring (Contemporary Mathematics, 2024)
The management of aviation gate assignments may significantly affect the overall productivity of an airport. This work presents a novel approach to enhancing gate assignment algorithms. The methodology used in this study incorporates graph theory and other intricate techniques, with specific focus on the concept of local antimagic vertex coloring. This study presents a comprehensive methodology for identifying optimal gate locations, which incorporates several factors such as aircraft characteristics, passenger capacity, and resource availability. Based on the results of this study, the incorporation of local antimagic vertex coloring exhibits the capacity to significantly enhance the operational effectiveness of airports via the reduction of passenger line wait times and alleviation of traffic congestion challenges. The aforementioned result was derived by using comprehensive models of the physical cosmos and conducting a meticulous analysis of empirical facts. This novel concept has the capacity to enhance the efficacy of airport gate allocation, resulting in heightened levels of customer contentment and reduced operational costs. The implementation of this procedure will facilitate the preservation of the efficiency of the operational networks for air transportation.
Keywords: airport; flight-gate allocation; local antimagic vertex coloring; congestion minimization; adaptability; airport operations